Cultura organizacional na gestão da qualidade e segurança do paciente em um hospital público universitário - Palloma Fernandes Estanislau Vaz Ventura (2020)
The influence of organizational culture in the management of patient quality and safety has become the object of study, as it is essential for hospital management, as it involves subjective issues in addition to assessment and monitoring techniques. The general objective of the study is to analyse the influence of organizational culture on quality management and patient safety in a public university hospital in Belo Horizonte and in the daily work of professionals. And, as specific objectives: to understand aspects of the hospital's culture from its historical evolution and ongoing changes; identify the understanding of organizational culture by the professionals of the multidisciplinary team and the nursing team; identify the conceptions of nursing professionals and staff about quality of care and patient safety and understand the view of health professionals about the influence of culture on quality management and patient safety. A single case study, with a qualitative approach, using the theoretical framework of Fleury and Fischer, in the medical clinic units of Hospital das Clínicas, Federal University of Minas Gerais. Eighteen managers participated, 12 nurse assistants, 1 nurse of the Infection Control Commission, 1 nurse of nutritional support, 11 nursing technicians, 1 clinical pharmacist, 1 speech therapist, 1 physiotherapist, 2 social workers, 1 medical professor and 2 physicians on duty, totaling 51 respondents. Data were collected through observation, document analysis and individual interviews with a semi-structured script. The interviews were scheduled, held in a private environment after clarification about the research, authorization to record and signing the Informed Consent Form. The data were submitted to thematic content analysis. Four categories of analysis were organized: Political economic instance: comprising symbolic elements; Instance of human resources management policies; Instance of the organization of the work process; and Quality management and patient safety. The symbolic elements constituting the culture identified were: power of the teacher, the doctor, the strength of the university's culture, collegial decisions, the stability and autonomy of the statutory bodies of the Single Legal Regime, myth of the 7th floor medical clinic, work overload and insufficient dimensioning and the myth of the public service. Such elements influence the management of quality and patient safety because the proposed actions do not have adherence to consolidate themselves in the daily work, and it is surrounded by the current discourse of not giving time, it has always been like this and it really takes time here, it is public service , even with the entry of Empresa Brasileira Serviços Hospitalares and the proposal for a new care and management model. It is concluded that the symbolic elements determine the work process and the relationship between people, consolidating the structures of current power, guaranteeing the maintenance of actions in the daily work of professionals.